Can heart rate variability be used to monitor neuromuscular fatigue in strength and conditioning - O`Brien, D. P. (Journal of Australian Strength and Conditioning, 2017)
Heart rate variability has emerged recently as an effective means for testing both clinical and general populations, and is gaining ground in testing athletic performance, and factors associated with decreases in performance. HRV, the term given to the variability of the timing between heart beats, has been widely regarded as an effective method of establishing the inhibition of the parasympathetic nervous system, and increasing dominance of the sympathetic nervous system. This relationship can be applied to the state of athletes in potentially over-training situations. The relationship between low HRV (<0.15Hz), and over-training, as well as factors noted during extended periods of fatigue, provides stable ground for the use of HRV, and assessing levels of neuromuscular fatigue, experienced by athletes during conditioning phase of periodization. The state of the ANS has been associated with symptoms of neuromuscular fatigue, such as altered state of T:C ratio, sleep quality and deprivation, muscle soreness, illness, and injury rates. 33 articles were reviewed, to determine the likelihood that HRV could be used in an S&C setting, to assess levels of neuromuscular fatigue in athletes, determinable by HRV measurements. From the literature, it was concluded that although the research between strength and conditioning, and increased sympathetic nervous system activity is minimal, there is more than enough evidence to suggest that HRV could be used as a means of monitoring neuromuscular fatigue in periods of strength and conditioning.